Practice characteristics of Emergency Department extracorporeal cardiopulmonary resuscitation (eCPR) programs in the United States: The current state of the art of Emergency Department extracorporeal membrane oxygenation (ED ECMO). (October 2016) - Tonna, Joseph E.; Johnson, Nicholas J.; Greenwood, John; Gaieski, David F.; Shinar, Zachary; Bellezo, Joseph M.; Becker, Lance; Shah, Atman P.; Youngquist, Scott T.; Mallin, Michael P.; Fair, James Franklin; Gunnerson, Kyle J.; et al.
Abstract: Purpose: To characterize the current scope and practices of centers performing extracorporeal cardiopulmonary resuscitation (eCPR) on the undifferentiated patient with cardiac arrest in the emergency department. Methods: We contacted all US centers in January 2016 that had submitted adult eCPR cases to the Extracorporeal Life Support Organization (ELSO) registry and surveyed them, querying for programs that had performed eCPR in the Emergency Department (ED ECMO). Our objective was to characterize the following domains of ED ECMO practice: program characteristics, patient selection, devices and techniques, and personnel. Results: Among 99 centers queried, 70 responded. Among these, 36 centers performed ED ECMO. Nearly 93% of programs are based at academic/teaching hospitals. 65% of programs are less than 5 years old, and 60% of programs perform ≤3 cases per year. Most programs (90%) had inpatient eCPR or salvage ECMO programs prior to starting ED ECMO programs. The majority of programs do not have formal inclusion and exclusion criteria. Most programs preferentially obtain vascular access via the percutaneous route (70%) and many (40%) use mechanical CPR during cannulation. The most commonly used console is the Maquet Rotaflow ® . Cannulation is most often performed by cardiothoracic (CT) surgery, and nearly all programs (>85%) involve CT surgeons, perfusionists, and pharmacists. Conclusions: Over a third of centers that submitted adult eCPR cases to ELSO have performed ED ECMO. These programs are largely based at academic hospitals, new, and have low volumes. They do not have many formal inclusion or exclusion criteria, and devices and techniques are variable.